Synthesis and characterization of plant extracted silver nanoparticles and advances in dental implant applications - Nayem Hossain; Mohammad Aminul Islam; Mohammad Asaduzzaman Chowdhury (Heliyon, 2022)
Dental implantology has always emphasized silver nanoparticles (AgNPs) for various applications due to their biocompatibility, antibacterial activity, and increased surface volume ratio offered by these particles. It is utilized to a large extent in the dental implant industry as a surface modification, biocompatible constituent and composite material. AgNPs may be produced inexpensively, sustainably, and environmentally responsibly by utilizing technologies that extract the plant material. The phytochemical components that are contained in plants make them a better, non-toxic, and more cost-effective alternative to both physical and chemical approaches. Because the size and shape of AgNP depend on their synthesis method and technique, and because the efficacy and toxicity of AgNP depend on both size and shape, synthesis methods and techniques have recently become the focus of a significant amount of research attention. In this review, we discussed Plant Extracted Ag-NP's whose sizes range up to 100nm. This review also focuses on recent research advancements in the Plant Extracted synthesis of AgNPs, as well as their characterization methodologies, current obstacles, future possibilities, and applications in dental implantology.